Bahasa Inggris - Afriani, Afriani; Auliandari, Ela; Aziz, Abdul; Alwi, Yun (Universitas Bengkulu, 2025)
Broiler chicken meat is a highly nutritious protein source that has a good taste, a delicious smell, a soft texture and is relatively inexpensive. Despite these benefits, it is a perishable food. To address this issue, cold temperature storage can be utilised as a strategy to mitigate the damage. The objective of this study was to determine the physical quality and total microbes of broiler meat stored in a refrigerator before storage in a frozen state. This study was conducted using a Completely Randomized Design (CRD) with four treatments and five replicates. The treatment involved the length of cooling in the refrigerator (± 5°C) before frozen storage, which was set at 0, 2, 4, and 6 hours. The parameters observed were pH, cooking loss, water binding capacity and total microbial count. The data were analysed using the Analysis of Variance (ANOVA) and Duncan's Multiple Range Test (DMRT). The results revealed that the duration of refrigerated storage had a significant effect (P<0.05) on the pH value, water binding capacity, cooking loss, and total microbes. The treatment P0 (without refrigeration) resulted in the highest pH value, the lowest water binding capacity, and a low cooking loss and total microbes. The refrigeration of broiler chicken thigh meat was observed to reduce pH value, increase water binding capacity, reduce cooking loss and increase total microbes. Therefore, refrigerating broiler chicken thigh meat for 6 hours before frozen storage can maintain the meat's quality.